Nivel de satisfacción del paciente adulto mayor sobre el cuidado que brinda la enfermera en el servicio de medicina del Hospital II 2 Minsa- Tarapoto. periodo Junio - Julio 2012 - López Amasifén, Wendy Fiorella (2012)
The present study: Level of satisfaction of the patient Major adult on the care that the nurse offers in the service of Medicine of the Hospital the IInd- 2 MINSA - TARAPOTO. These investigation was realized in Period June - July, 2012; It had as objective: To determine the level of Satisfaction of the Major adult Patient on the care that the Nurse offers in the Service of Medicine of the Hospital the IInd -2 MINSA - TARAPOTO. Period June - July, 2012. The Methodological Design was an applicative investigation of the descriptive simple of transverse court, in which the scale will be in use as instrument. The sample considered for the study of investigation was shaped by 30 patients Major Adults who are hospitalized in the Services of General Medicine of the Hospital the IInd -2 MINSA - TARAPOTO. The conclusions in the present study were: The patient Major adult presents in major percentage a HIGH level of satisfaction on taken care that the nurse offers in the service of Medicine of the HII2 MINSA - TARAPOTO.